2024
DOI: 10.1117/1.nph.11.1.015004
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the performance potential of speckle contrast optical spectroscopy and diffuse correlation spectroscopy for cerebral blood flow monitoring using Monte Carlo simulations in realistic head geometries

Mitchell B. Robinson,
Tom Y. Cheng,
Marco Renna
et al.

Abstract: The non-invasive measurement of cerebral blood flow based on diffuse optical techniques has seen increased interest as a research tool for cerebral perfusion monitoring in critical care and functional brain imaging. Diffuse correlation spectroscopy (DCS) and speckle contrast optical spectroscopy (SCOS) are two such techniques that measure complementary aspects of the fluctuating intensity signal, with DCS quantifying the temporal fluctuations of the signal and SCOS quantifying the spatial blurring of a speckle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Although an s∕p ratio of two or above is typically used to perform speckle imaging, here we are interested in extracting the dynamics of the scattering medium via speckle statistics. Toward this end, it has previously been shown that maximum SNR can occur at s∕p ratio close or lower than one 16,37,38 (see Supplementary Material for more details).…”
Section: Methodsmentioning
confidence: 99%
“…Although an s∕p ratio of two or above is typically used to perform speckle imaging, here we are interested in extracting the dynamics of the scattering medium via speckle statistics. Toward this end, it has previously been shown that maximum SNR can occur at s∕p ratio close or lower than one 16,37,38 (see Supplementary Material for more details).…”
Section: Methodsmentioning
confidence: 99%